2019
DOI: 10.1021/acs.est.8b03675
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Zn in Agricultural Soils: A Stable Isotope Approach to Anthropogenic Impact, Soil Formation, and Soil–Plant Cycling

Abstract: The supplementation of Zn to farm animal feed and the excretion via manure leads to an unintended Zn input to agricultural systems, which might compromise the long-term soil fertility. The Zn fluxes at three grassland sites in Switzerland were determined by a detailed analysis of relevant inputs (atmospheric deposition, manure, weathering) and outputs (seepage water, biomass harvest) during one hydrological year. The most important Zn input occurred through animal manure (1,076 to 1,857 g ha-1 yr-1) and Zn mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…This additional TE term, being a calibrated variable, was attributed to mineral weathering, although the site history also suggests that there is likely to be a contribution from inputs of fungicides to the labile Cu concentrations at the beginning of the measurement period. Estimates of TE weathering rates of 0.001-0.86 mg m -2 yr -1 for Zn and 0.0-0.039 mg m -2 yr -1 for Cd in Swiss agricultural soils have been reported (Imseng et al, 2018;Imseng et al, 2019), which were consistent with the fitted values. However, there is a need for more research on topsoil metal weathering rates and their contribution to determining labile metal concentrations in order to reduce the overall uncertainty on historic TEs inputs.…”
Section: Simulations Of Soil Metal Dynamicssupporting
confidence: 78%
“…This additional TE term, being a calibrated variable, was attributed to mineral weathering, although the site history also suggests that there is likely to be a contribution from inputs of fungicides to the labile Cu concentrations at the beginning of the measurement period. Estimates of TE weathering rates of 0.001-0.86 mg m -2 yr -1 for Zn and 0.0-0.039 mg m -2 yr -1 for Cd in Swiss agricultural soils have been reported (Imseng et al, 2018;Imseng et al, 2019), which were consistent with the fitted values. However, there is a need for more research on topsoil metal weathering rates and their contribution to determining labile metal concentrations in order to reduce the overall uncertainty on historic TEs inputs.…”
Section: Simulations Of Soil Metal Dynamicssupporting
confidence: 78%
“…To this end, a multicollector ICPMS (MC-ICPMS) is used that achieves a precision of 0.01% relative standard deviation (RSD) for isotope ratio measurements which is adequate to study natural biogeochemical fractionation processes (Cloquet et al, 2008; Caldelas and Weiss, 2017). Analysis of such natural variations has allowed source tracing of metals on field or catchment scales (Borrok et al, 2009; Bigalke et al, 2010; Imseng et al, 2019; Yang et al, 2019). However, this approach requires that the isotope ratios of sources and sinks are distinguishable, which is not always the case (Wiggenhauser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that soil Zn had a minor impact on Zn plant uptake, since soil Zn was about two times as high in the Strickhof compared with the Heitenried soil ( Table 1 ). The higher soil pH, and likely the higher carbonate concentration, in the Strickhof soil may have reduced the solubility of Zn derived from the fertilizer and soil due to a stronger adsorption of Zn on negatively charged binding sites of the soil (Diesing et al, 2008 ; Imseng et al, 2019 ). The lower solubility of fertilizer Zn and soil Zn in the alkaline Strickhof soil may have further lowered the concentration and uptake of Zn in the ryegrass shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Complex organic fertilizers such as sewage sludge, animal manure, and compost are known sources of heavy metals such as zinc (Zn) in agroecosystems (Nicholson et al, 2003 ; Imseng et al, 2019 ). Bolan et al ( 2004 ) reported that the concentration of Zn in animal manure and sewage sludge ranged from 1.8 to 6480 mg kg −1 (median 378 mg kg −1 ).…”
Section: Introductionmentioning
confidence: 99%